The effect of dust on photovoltaic thinfilm modules - Hassan Qasem; Tom Betts; Ralph Gottschalg (2011)
This paper investigates the effect of dust on Cadmium Telluride (CdTe) photovoltaic (PV) modules by the use of a Spatial 3 Dimensional Model (S3DM) with circuit analysis software PSPICE. The investigation was carried out to look into the effect of dust concentration and tilt angle variation on the PV module. It also looks into the possibility of hotspot effect due to different installation positions under dusty conditions. The simulation results showed a reduction in the sample performance with increased dust concentration and reduced tilt angle. The variation between cell positions showed that cells in configuration where they are oriented in a horizontal position to the plane tended to lead to hotspots when both low shunt cells and high shunt cells are identified, with cells identified with lower shunts being the more vulnerable.